Obtención de un aceite esencial a partir de la semilla del mango utilizando el método de extracción con solventes (2020)
The present work aims to compile and present the methodology used to carry out the process of obtaining an essential oil starting from mango seed, this document is only theoretical, but serves as a basis for future projects. Starting the essential oil of the mango seed is a good ally for the skin care as it contains multiple vitamins and helps regeneration of this, for this reason it is decided to carry out the project from this waste with the in order to find new alternatives for waste management helping the industry reducing the quantity and cost of disposing of these. The project presents an analysis of bibliographic sources to determine the properties physicochemicals of the raw material handled, the methodology to follow for the obtaining essential oil applying extraction with solvents, specifically the soxhlet method is discussed, as well as identifies and describes the previous processes (drying and grinding) to the extraction so that the matter is in optimal conditions for the process. A basic conceptual design is also developed from theoretical data that describes the stages of the process, a selection of equipment necessary for each stage with general specifications and in turn a mass balance by operation, subsequently based on this design an analysis of costs taking into account capital and operating costs here.